2021
DOI: 10.1002/ece3.8089
|View full text |Cite
|
Sign up to set email alerts
|

Depth diversity gradients of macrophytes: Shape, drivers, and recent shifts

Abstract: Investigating diversity gradients helps to understand biodiversity drivers and threats. However, one diversity gradient is rarely assessed, namely how plant species distribute along the depth gradient of lakes. Here, we provide the first comprehensive characterization of depth diversity gradient (DDG) of alpha, beta, and gamma species richness of submerged macrophytes across multiple lakes. We characterize the DDG for additive richness components (alpha, beta, gamma), assess environmental drivers, and address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 86 publications
2
2
0
Order By: Relevance
“…Single scale and single dimension are not appropriate to depict the patterns of species richness (Mirochnitchenko et al 2021). In line with other studies (Mellin et al 2010, Ruiz‐Benito et al 2012, Toledo et al 2012, Lewerentz et al 2021), we see that the multidimensionality of environmental gradients across lake types are worth disentangling to understand species richness patterns.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Single scale and single dimension are not appropriate to depict the patterns of species richness (Mirochnitchenko et al 2021). In line with other studies (Mellin et al 2010, Ruiz‐Benito et al 2012, Toledo et al 2012, Lewerentz et al 2021), we see that the multidimensionality of environmental gradients across lake types are worth disentangling to understand species richness patterns.…”
Section: Discussionsupporting
confidence: 91%
“…Our results show for the first time that the empirically observed hump‐shaped pattern of species richness along depth (Lewerentz et al 2021) already emerge solely from eco‐physiological processes (Fig. 2a, b).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Surprisingly, obligate wetland species richness (OBL) did not differ between wet basins and ponds, even though the area permanently submerged in ponds is much greater. Stormwater infrastructures in urban areas may not be appropriate for attracting a high richness of OBL species because of urban pressures, such as high turbidity and nutrient concentration, or the high pond water levels that leaves little space for the establishment of wetland plants (Akasaka et al 2010;Lewerentz et al 2021;Mackintosh et al 2015). However, a higher proportion of OBL was found in ponds compared to wet basins, certainly due to the permanent presence of water, favorable to the establishment of these species while limiting others.…”
Section: Water and Bank Area Drive Local Vegetation Diversity And Com...mentioning
confidence: 99%
“…With the increasing water depth, the absorption and scattering of light in water increases (Middelboe and Markager, 1997), creating stronger light-limited conditions. Previous studies have revealed that increasing the water depth negatively affects species richness (Fu et al, 2014a;Ye et al, 2018;Lewerentz et al, 2021;Ma et al, 2021). Additionally, some studies have shown that the relationship between community biomass and water depth is unimodal or is either negative or positive (Fu et al, 2014a;Dong et al, 2014;Bolpagni et al, 2016;Ye et al, 2018;Wang et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%